2009
DOI: 10.1177/1363461509105819
|View full text |Cite
|
Sign up to set email alerts
|

Problemas de Nervos: A Multivocal Symbol of Distress for Portuguese Immigrants

Abstract: This article outlines research on a previous unstudied form of suffering specific to the Portugese immigrant community: problemas de nervos. Thirty-two Portuguese immigrant women (in Waterloo, ON and Boston, MA) were interviewed and each completed a questionnaire. Cluster analysis demonstrated that problemas de nervos has many meanings. The study profiled symptoms, causes and therapies associated with four variations of this culture-specific form of distress: "mal da cabeca" meaning problems with/in the head (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 23 publications
0
13
0
5
Order By: Relevance
“…The purpose of this research was to examine and discover what relationships exist among acculturation and family in the Portuguese immigrant population in Canada as these topics were the most prevalent in our previous research with Portuguese immigrants (James, 2002). We discovered that in response to background questions asked of interviewees for other research (James, Navara, Foster, Fernandes, & Harris, 2009), rich depictions of family processes within acculturation were present and were left unanalyzed. See Appendix A for the list of background interview questions.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this research was to examine and discover what relationships exist among acculturation and family in the Portuguese immigrant population in Canada as these topics were the most prevalent in our previous research with Portuguese immigrants (James, 2002). We discovered that in response to background questions asked of interviewees for other research (James, Navara, Foster, Fernandes, & Harris, 2009), rich depictions of family processes within acculturation were present and were left unanalyzed. See Appendix A for the list of background interview questions.…”
Section: Methodsmentioning
confidence: 99%
“…The worldwide phenomenon of immigration, mixing cultures, and acculturation brings with it various challenges to physical and mental health, including issues related to sleep (Holroyd, Molassiotis, Taylor-Pilliae, 2001; James, Fernandes, Nevara, Harris, & Foster, 2009; Maty, Leung, Lau, & Kim, 2010). Latinos comprise the largest minority group in United States (US) (US Census, 2010b), and numbers are predicted to nearly triple by 2050 (US Census, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Our work with Portuguese immigrants in North America revealed that traditional psychiatric categories are limited when trying to classify Portuguese idioms of distress (James et al, 2009) such as agonias (James and Clarke, 2001; James, 2002; James and Prilleltensky, 2002; James et al, 2006). Our research into agonias included Portuguese men and women who came from the Azorean Islands and who are now living in the United States (James, 2002) and Canada (James et al, 2005).…”
Section: Study 1: the Individual Domainmentioning
confidence: 98%